(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This article is devoted to the problems of healthcare management in Uzbekistan. It analyzes contemporary problems related to the management of the healthcare system in Uzbekistan (financing, human resources, primary health care, infrastructure, information systems, quality control and transparency of management) and as solutions to these challenges, it is proposed to update the legal framework, increase transparency in financial mechanisms, motivate medical personnel, and widely implement digital technologies in healthcare.provides practical recommendations for modernizing the system.